LEGAL CERTAINTY OF BPJS KESEHATAN CARD REQUIREMENTS IN THE TRANSFER OF LAND RIGHTS - Teguh Ariyanto; Gunawan Djajaputra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This article aims to analyze and examine the legal certainty of the prerequisites for the BPJS card in transferring land rights and the legality of transferring land rights without attaching a BPJS card after Presidential Instruction No. 1 of 2022. This article uses a normative legal research method. The nature of the research is descriptive analysis. The primary legal materials used in this writing are the 1945 Constitution of the Republic of Indonesia, Law Number 5 of 1960 concerning Basic Agrarian Regulations, Government Regulation Number 24 of 1997 concerning Land Registration, and Government Regulation of the Republic of Indonesia Number 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration and Presidential Instruction Number 1 of 2022 concerning Optimization of the Implementation of the National Health Insurance Program. As for secondary legal materials in the form of publications on law including text books, legal dictionaries, legal journals, and comments on court decisions. The tertiary legal materials used in this study are the Big Indonesian Dictionary and the Legal Dictionary. The results of the study show that legal certainty is a prerequisite for BPJS cards in transferring land rights, namely the government does not actualize aspects of legal certainty as prerequisites for BPJS cards in transferring land rights where legal regulations must be implemented consistently and consequentl.